The Effect of Ship Crew Competence, Towing Premium Compensation and Ship Crew Retention On Ship Crew Performance Case Study at PT Varia Usaha Lintas Segara - Tiar Achdian (Jurnal Indonesia Sosial Teknologi, 2024)
The purpose of this research to identify the effect of ship crew competence, towing premium compensation and ship crew retention on ship crew performance case study at pt varia usaha lintas segara. This study used quantitative methods. The analysis method used in this study is multiple linear regression analysis method. This method is used to analyze the effect of ship crew competence, financial towing premium compensation and ship crew status on the performance of PT Varia Usaha Lintas Segara's crew. The conclusion of this study shows a significant positive influence of towing premium compensation, ship crew competence, and ship crew retention on ship crew performance at PT Varia Usaha Lintas Segara. Multiple linear regression analysis shows that towing premium compensation has a significant positive influence on crew performance, along with increased crew retention. Furthermore, the improved competence of ship crews also contributes significantly positively to their performance, increasing crew retention.